The Use of Women’s Language Features in March Family with References “Little Women” Movie - Wulandari, Luh Made Sintya (Program Magister Linguistik Universitas Udayana, 2024)
This study aimed to identify the types of women’s language features used in Little Women Movie using the theory proposed by Lakoff (1973) and explain the reason of women characters used each women’s language features based on the theory by Holmes (2013). The data source is a movie entitled Little Women, which was released on February 7, 2020. Documentation and note-taking method were applied in order to collect the data. The descriptive qualitative method was used in analyzing the data since the data were analyzed in the form of sentences and paragraphs. The analysis of this study was presented using formal and informal methods. The results showed all women’s language features based on Lakoff (1973) found in this movie. Those are fillers and hedges, tag questions, rising intonation, empty adjectives, intensifiers, hypercorrect grammar, ‘superpolite’ forms, avoidance of strong swear words, and emphatic stress. Meanwhile, the reasons women talk using women’s language features mentioned by Holmes (2013) were also found in the women characters, including social conscious, woman’s role as guardians of society’s values, and subordinate group. Keywords— Language and Gender, Women’s Language Features, Little Women.